Metode Falsafat: Alternatif Pemetaan Realita Kehidupan Sosial Keagamaan - Syamsul Rijal (Islam Futura, 2001)
Socio-religious reality constitutes a phenomenon arising from social interaction and people's understanding of their religion. Hence, a study of social life, through its various methods, is extremely urgent in order to comprehend the reality itself that eventually will enrich one’s ability in absorbing philosophical methods. This article, therefore, tries to provide approaches in comprehending socio-religious phenomena in the community.